Ethical and Philosophical Aspects of Nursing Children and Young People - Brykczynska, Gosia M. (John Wiley & Sons, Ltd, 2011)
Nurses and healthcare professionals are constantly faced with ethical and philosophical dilemmas when working with children in everyday practice. Ethical and Philosophical Aspects of Nursing Children and young people is a comprehensive text on the ethics and philosophy behind paediatric nursing, that reflects some of the contemporary issues encountered while working with children and young people. This important new book provides a philosophical and historical analysis of the subject, looking at a review of sociological and political theories concerning the nature of childhood, and providing a